Granted as a management instrument for the use of water resources in the Baixo Teles Pires river basin (Research, Society and Development, 2024)
Located in a region of broad geoenvironmental diversity, the lower Teles Pires river basin is undergoing transformations in territorial occupation driven by economic development. This highlights the importance of the need to monitor these changes. Therefore, the objective of this study is to conduct an investigation of water uses in the basin region by quantifying the concessions granted for the capture of surface and underground water. A consultation was carried out in databases in the Geoportal system of the State Secretariat for the Environment (SEMA/MT), as well as in the National Water Resources System (SNIRH), of the National Water and Basic Sanitation Agency (ANA), with the objective of quantifying and classifying surface and underground concessions according to their use. It was found that the majority of surface catchment permits in the basin area were issued for irrigation, basic sanitation and public supply, corresponding to 37% of use each. As for underground grants, it was found that 36% were issued for human consumption. However, the considerable difficulty in accessing the water resources information system became evidente.